Biochemical, hematologic, and skeletal features associated with underweight, overweight, and eating disorders in young Korean women: A population-based study - An, Zhen; Kim, Kyung-Hee; Kim, Mirihae; Kim, Youl-Ri (Frontiers in Psychiatry, 2022)
Background: Extreme weight conditions in young women are associated with adverse health outcomes. Closely linked with extreme weight status, eating disorders (EDs) are associated with several medical complications and high mortality rates. Objective: The study aimed to investigate the biochemical, haematologic, and skeletal features of young Korean women with underweight (UW) and overweight/obesity (OW) conditions, and patients with anorexia nervosa (AN) and bulimia nervosa (BN) compared to women with normal-weight (NW). Method: A total of 808 women (mean age 22.3 ± 3.4 years) were recruited for the study, including 144 with UW status [body mass index (BMI) < 18.5 kg/m2], 364 with NW, 137 with OW or obesity (27 with obesity; BMI ≥ 25 kg/m2), 63 patients with anorexia nervosa (AN), and 100 with bulimia nervosa (BN). We measured blood pressure and performed biochemical, haematologic and bone mineral density (BMD) evaluations at the lumbar and femoral neck. Results: Blood pressure and triiodothyronine levels were found to be lower in both ED groups and higher in the OW group, but no difference in the UW group, compared to the NW group. The aminotransferases and total cholesterol levels were higher in the ED and OW groups, compared to the NW group. Blood cell counts were decreased in the AN group, while increased in the OW group, compared to the NW group. Blood urea nitrogen was elevated in both ED groups. The UW and AN groups had lower BMD, whereas the OW group had higher BMD, compared to the NW group. Conclusion: Our findings suggested that both ED groups were associated with decreases in the resting energy expenditure. OW status was associated with a risk of metabolic syndrome, and UW status with lower BMD in young women. Overall, the medical parameters in Korean patients with ED were similar to the patterns reported in Western samples in previous studies, with few exceptions such as potassium level in BN.